Optimizing Hospitality Choices: A Forward Chaining and Certainty Factor-Based Expert System for Recommending 4-Star Hotels in Batam City - Caniago, Deosa Putra; Simatupang, Devid Trinaldo; Kurnia, Okki; Septiana, Reski; Sekar, M. Y. Meinadia (AI Society & STMIK Indonesia, 2024)
Tourism and travel is the largest industry in the world with hotels as a key factor in enjoying a holiday. As the cornerstone of tourism, the hotel industry continues to develop to meet increasingly high customer expectations. The application of high technology is the key to competition between hotels, with several hotels moving towards an innovative and efficient